(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
In tropical aquatic ecosystems, temporal climate patterns shape environmental conditions and biodiversity. However, the impact of these changes on aquatic communities in the Neotropics has been understudied. This research evaluates how the variation between dry and rainy seasons affects water quality and the alpha and beta diversity of aquatic insects in the Cuitzmala and Purificación river basins in Jalisco, Mexico. The results show a clear influence of the seasons on water quality and insect diversity patterns. During the dry season, higher levels of electrical conductivity, salinity, and dissolved solids are observed, while during the rainy season, turbidity and phosphate levels increase. Alpha diversity is higher in the dry season, and beta diversity shows greater turnover of insect families in the dry season and greater nestedness in the rainy season. These findings indicate that aquatic communities respond differently to seasonal conditions, which may affect the resilience and ecological stability of these ecosystems.